2013
DOI: 10.1002/dvdy.23919
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Canonical WNT Signaling Pathway Promotes Ovarian Surface Epithelial Proliferation Without Inducing β‐Catenin/Tcf‐Mediated Reporter Expression

Abstract: Background: In response to activation of the canonical WNT signaling pathway, b-catenin cooperates with Lef/Tcf (lymphoid enhancer factor/T-cell factor) transcription factors to drive expression of Wnt target genes. The canonical WNT signaling pathway is involved in development, wound repair, and tumorigenesis. Studies examining the involvement of the canonical WNT signaling pathway in the development of ovarian surface epithelium (OSE) and ovarian carcinogenesis, however, have recently begun to emerge. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Our observation corroborates with the finding that report activity of GSK3β is required for SKOV-3 cell survival (Cao et al, 2006). Furthermore, it has been demonstrated that LiCl or Wnt3a has no effect on β-catenin/Tcf reporter activity in SKOV-3 cells (Usongo et al, 2013). In addition, we showed recently that cell viability of SKOV-3/Wnt5a was increased by 30% compared to mock.…”
Section: Substrate-dependent Cell Adhesion Assay In the Presence Of Rsupporting
confidence: 92%
“…Our observation corroborates with the finding that report activity of GSK3β is required for SKOV-3 cell survival (Cao et al, 2006). Furthermore, it has been demonstrated that LiCl or Wnt3a has no effect on β-catenin/Tcf reporter activity in SKOV-3 cells (Usongo et al, 2013). In addition, we showed recently that cell viability of SKOV-3/Wnt5a was increased by 30% compared to mock.…”
Section: Substrate-dependent Cell Adhesion Assay In the Presence Of Rsupporting
confidence: 92%
“…β-catenin in nuclei binds to the TCF/LEF in several types of cancers for transcriptional activation of downstream genes, such as cyclinD1, c-myc and MMPs [15][21], which play important roles in carcinogenesis and metastasis. To explore the effect of DACT2 on Wnt signaling in human thyroid cancer, Topflash and (TCF/LEF) reporter system was employed.…”
Section: Resultsmentioning
confidence: 99%
“…Although the interaction mechanism between GAD1 and β-catenin has not yet been reported, the current data suggested that GAD1 expression controls β-catenin localization. β-catenin in nuclei binds to the TCF/LEF in several types of cancers for transcriptional activation of downstream genes, such as MMP7 , cyclinD1 , and c-myc [42-46], which play important roles in carcinogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%